2‐substituted tricyclic oxazolo[5, 4‐d]pyrimidine library: Design, synthesis, and cytotoxicity activity. (24th November 2021) - Zeng, Yan; Nie, Lifei; Bozorov, Khurshed; Ruzi, Zukela; Song, Buer; Zhao, Jiangyu; Aisa, Haji Akber
Abstract: We report the design, synthetic route, and cytotoxicity of a library of 49 newly synthesized tricyclic oxazolo[5, 4‐ d ]pyrimidines. The condensed pyrimidinones were constructed from ethyl 5‐aminooxazole‐4‐carboxylate building blocks. A tricyclic ring system was built using the naturally occurring mackinazolinone alkaloid with a focus on the molecular diversity at position C‐2 of the oxazole ring. Synthesized compounds were evaluated against a panel of human cancer cell lines including MCF‐7 (breast), HeLa (cervical), and A549 (lung) in vitro. The results revealed that substitution of halogen‐related aromatic fragments at position C‐2 of the oxazole ring may serve as promising anticancer drug candidates. Abstract : Based on the general framework of Mackinazolinone alkaloid from natural products, forty‐nine tricyclic oxazolo[5, 4‐d]pyrimidine derivatives were designed and synthesized. Focused on the diversity of substituents on the position C‐2 of oxazole ring. Synthesized compounds were evaluated for the cytotoxic activity on three strains of cancer cells and two strains of normal cells. The results revealed that presence of chlorine at meta position of the benzene ring enhance the activity, and compound 7ap exhibited the best inhibitory activity against A549 cell lines with an IC50 of 0.75±0.06 µM.